Download presentation
Presentation is loading. Please wait.
Published byAbigail Copeland Modified over 9 years ago
1
Snapshot of the School Year Algebra 2 Honors Class Alex Asemota Mrs. Vittese Period 4 May 3, 2012
2
Chapter 2 To solve this problem: 2x-3 11 Solve the first inequality: 2x-3<5 (Add 3 on both sides) 2x<8 (Now divide by 2 on both sides) x<4 Then solve the second inequality: x+14>11 (Subtract 14 from both sides x>-3 The solution is: x>-3 and x<4 This means that all numbers between -3 and 4 are solutions.
3
Chapter 3 Find function composition given f(x) = 3x and g(x) = x + 2. Question: f(g(8)) Step 1: Plug in given for x and solve. g(8) = (8) + 2 = 10 Step 2 : Plug in g(4) for into f function and solve. f(g(8)) = f(10) = 3(10) = 30
4
Chapter 4 Solve 4x + 3y = 19 and 5x + 7y = 40 Step 1: Multiply equations to make the coefficients of the x terms additive inverses. 5 (4x + 3y) = 5 19 −4 (5x + 7y) = −4 40 Step 2: Simplify, 20x + 15y = 95 −20x − 28y = −160 Step 3: Then you have to divide to get y −13y = −65 y = 5 Step 4: Substitute for y in the first equation to get x 4x + 3(5) = 19 4x = 4 x = 1 The solution is (1, 5).
5
Chapter 5 Solve: x 2 + 5x + 7x + 35 Step 1: Put related terms next to each other x(x + 5) + 7(x + 5) = Step 2: Simplify (x + 7)(x + 5)
6
Chapter 6 Solve: x + 9/x = 10 x(x + 9/x)=10 Step 1:Multiply through by x to clear the fractions. x 2 + 9 = 10x Step 2: Subtract 10x to make it all equal 0. x 2 − 10x + 9 = 0 Step 3: Factor (x − 1)(x − 9) = 0 Step 4: Solve for 0 x = 1 OR x = 9 Step 5: Check answer Both 1 and 9 check in the original equation. The solutions are 1 and 9.
7
Chapter 7 Solve:´√ 3x+3 + √ x+2 = 5 Step 1: Subtract √ x+2: √ 3x+3=- 5 − √ x+2 ( √ 3x+3) 2 = (5 − √ x+2) 2 Step 2: Square the terms, 3x + 3 = 25 − √ x+2 + x + 2 Step 3: Simplify 10 √ x+2 = 24 − 2x Step 4: Factor and Divide 5 √ x+2 = (12 − x) Step 5: Square to to cancel square roots (5 √ x+2) 2 = (12 − x) 2 Step 6-9: Simplify and Solve 25(x + 2) = 144 − 24x + x2 25x + 50 = 144 − 24x + x2 0 = 94 − 49x + x2 0 = (x − 2)(x − 47) x = 2 OR x = 47 Step 10: Check 2 checks in the original equation; 47 does not check. The solution is 2.
8
Chapter 8 Solve: 5x2 + 6x + 1 = 0 Step 1 : Plug information for as in ax 2 + bx + c=0 Step 2: Simplify Answer: x = {-1/5, -1}
9
Chapter 9 Step 1: Start with the given equation Step 2: Subtract from both sides Step 3:Factor out the leading coefficient Step 4: Take half of the x coefficient Step 5:Now square Step 6: Now add and subtract this value inside the parenthesis. Doing both the addition and subtraction of does not change the equation Step 7: Distribute Step 8: Multiply Step 9: Now add to both sides to isolate y Step 10: Combine like terms Vertex (-1,6) AoS x= -1 Minimum is the vertex (-1,6)
10
Chapter 11 Using the Remainder Theorem, find the value of f (–5), for f (x) = 3x4 + 2x3 + 4x. I need to do the synthetic division, remembering to put zeroes in for the powers of x that are not included in the polynomial: Since the remainder is 1605, then, thanks to the Remainder Theorem, I know that: f (–5) = 1605.
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.